Identificação e caracterização dos fatores transcricionais da família AP2 / ERF envolvidos com os mecanismos associados ao estresse hídrico em Coffea canephora - Silva, Willian Geraldo da (2020)
Coffee is one of the most valuable agricultural products in the world and a second most traded commodity. In this scenario, Brazil stands out, being considered the largest coffee producer and exporter in the world. This culture represents a source of jobs and adds considerable volume to the country's revenue, and its importance for the local and global socioeconomic situation is indisputable. However, abiotic stresses, such as drought, are factors that significantly affect their production, which require the expression of stress-responsive genes, which are regulated by a network of transcription factors. The AP2 / ERF family is an extended family of plant transcription factors that share a well-conserved DNA binding domain. Thus, it is believed that the identification of the factors that control the defense and adaptation mechanisms are important for the sustainability of this culture. Thus, the aim of this work was to identify and characterize, through in silico analyzes, the transcription factors of the AP2 / ERF family in genomic sequences deposited in public databases of Coffea canephora. Analyzes were performed using public databases of plant species to search for reference proteins related to the transcription factors of the AP2 / ERF family and their orthologists. The search for conserved domains was performed using PFAM. The obtained sequences were classified in a phylogenetic tree made with MEGA X 5.1. 39 putative AP2 / ERF family proteins were identified in the predicted proteome of Coffea canephora. All proteins identified in the predicted proteome of Coffee canephora presented the conserved domain Apetala 2 (AP2). The analyzes showed that proteins conserved amino acids essential for protein function such as YRG and RAYD, which are located within each AP2 domain. The analyzes carried out in this work were able to identify and characterize the probable genes of the AP2 / ERF family in the genome of Coffea canephora. These findings open an avenue for studies for the verification and search for the involvement of the participation of these genes in the resistance of coffee to drought.